Utilização de lodo de esgoto na produção de mudas de aroeira-pimenteira - Trigueiro, Rodrigo De Menezes (2014)
The objective of this study was to evaluate the feasibility of the sewage sludge used as substrate component for seedlings production of Brazilian pepper (Schinus terebinthifolius Raddi). The following proportions of sewage sludge/carbonized rice hull were tested, in tubes with 50 cm³: 80/20, 70/30, 60/40, 50/50 and 40/60, which were compared to a commercial substrate commonly used by forest nursery. Growth seedlings-related parameters were assessed: shoot height, collar diameter and accumulation of dry matter on the shoot and root, chemical analysis of shoot and root tissues. Schinus terebinthifolius seedlings developed in substrate with 40, 50 e 60% sewage sludge presented inferior growth compared to the control, however considering the parameters shoot height/collar diameter relation, production of dry matter on the shoot and root, and nutritional aspects, that attest to the quality of the seedlings, the results were satisfactory. Therefore, it was concluded that the use of this sewage sludge residue in the substrate composition for seedlings production of forest species is quite promising.